Pharmacological inhibition of the cysteine protease cathepsin C improves graft function after heart transplantation in rats - Baoer Liu; Brice Korkmaz; Patricia Kraft; Tobias Mayer; Alex A. Sayour; Marc A. Grundl; Roxane Domain; Matthias Karck; Gábor Szabó; Sevil Korkmaz-Icöz (Journal of Translational Medicine, 2023)
Abstract Background Heart transplantation (HTX) is the standard treatment for end-stage heart failure. However, reperfusion following an ischemic period can contribute to myocardial injury. Neutrophil infiltration, along with the subsequent release of tissue-degrading neutrophil elastase (NE)-related serine proteases and oxygen-derived radicals, is associated with adverse graft outcomes. The inhibition of cathepsin C (CatC) has been shown to block NE-related protease activation. We hypothesized that the CatC inhibitor BI-9740 improves graft function after HTX. Methods In a rat model of HTX, the recipient Lewis rats were orally administered with either a placebo (n = 12) or BI-9740 (n = 11, 20 mg/kg) once daily for 12 days. Donor hearts from untreated Lewis rats were explanted, preserved in a cardioplegic solution, and subsequently heterotopically implanted. In vivo left-ventricular (LV) graft function was assessed after 1 h of reperfusion. The proteolytic activity of neutrophil serine proteases was determined in bone marrow lysates from BI-9740-treated and control rats. Additionally, myocardial morphological changes were examined, and heart samples underwent immunohistochemistry and western blot analysis. Results The NE-related proteolytic activity in bone marrow cell lysates was markedly decreased in the BI-9740-treated rats compared to those of the placebo group. Histopathological lesions, elevated CatC and myeloperoxidase-positive cell infiltration, and nitrotyrosine immunoreactivity with an increased number of poly(ADP-ribose) polymerase (PARP)-1-positive cells were lowered in the hearts of animals treated with BI-9740 compared to placebo groups. Regarding the functional parameters of the implanted graft, improvements were observed in both systolic function (LV systolic pressure 110 ± 6 vs 74 ± 6 mmHg; dP/dtmax 2782 ± 149 vs 2076 ± 167 mmHg/s, LV developed pressure, at an intraventricular volume of 200 µl, p < 0.05) and diastolic function in the hearts of BI-9740 treated animals compared with those receiving the only placebo. Furthermore, the administration of BI-9740 resulted in a shorter graft re-beating time compared to the placebo group. However, this study did not provide evidence of DNA fragmentation, the generation of both superoxide anions and hydrogen peroxide, correlating with the absence of protein alterations related to apoptosis, as evidenced by western blot in grafts after HTX. Conclusions We provided experimental evidence that pharmacological inhibition of CatC improves graft function following HTX in rats.